The concise guide to the assessment and treatment of trauma-related dissociation - Brand, Bethany L. (Washington, DC American Psychological Association, 2024)
"Dissociation is one of the common sequelae of trauma, yet few clinicians have received training in evidence-based assessment and treatment of trauma-related dissociation (TRD). This book provides a concise overview of trauma-related dissociation, issues around misdiagnosis, methods for assessment, and guidance on treatment planning. Trauma-related symptoms and disorders are often overlooked or misconceptualized by mental health professionals. Failure to correctly diagnose and treat trauma-related dissociation can lead to prolonged suffering and a range of costs to individual clients and their loved ones, as well as to the health care system and society at large. Trauma-related dissociation is a symptom in a range of psychiatric disorders and is often associated with severe symptomatology and dysfunction, yet it can be successfully resolved if recognized and appropriately treated. This book addresses the lack of adequate training and knowledge about TRD by providing a systematic overview of methods for assessing it and a discussion of using assessment results to guide treatment planning. It provides a concise overview of conceptualizations of TRD and the reasons it is often overlooked or misdiagnosed, psychological disorders in which TRD is a key symptom, etiological theories of dissociation, the application of assessment data in treatment planning, issues specific to treatment of children and adolescents, and more topics that are imperative to understanding trauma-related dissociation"-- Provided by publisher.
Machine generated contents note: Series Foreword -- Anne P. DePrince and Ann T. Chu -- Foreword: The History and Complexity of Trauma-Related Dissociation -- John Briere -- Foreword: An Overview of The Concise Guide to the Assessment and Treatment of Trauma-Related Dissociation -- Frank W. Putnam -- Preface -- Chapter 1. An Introduction to Trauma-Related Dissociation -- Chapter 2. The Etiology of Dissociation -- Chapter 3. Therapeutic Approach to Assessing Trauma Exposure and Trauma-Related Dissociation -- Chapter 4. Self-Report Measures and Interviews for Assessing Dissociation -- Chapter 5. Assessing Dissociation in Forensic and Other Contexts in Which Malingering is Considered -- Chapter 6. Assessing Child and Adolescent Dissociative Disorders and Why It Matters -- Amie Myrick and Joyanna Silberg -- Chapter 7. Tailoring Treatment for Trauma-Related Dissociation -- References -- Appendix A. Diagnostic Interview Outline -- Appendix B. Assessment Measures: PITQ-t and PITQ-p -- Appendix C. Resources, Training, and Suggested Readings -- About the Author .
Includes bibliographical references and index.
Keywords: Dissociation (Psychology); Dissociative disorders; Dissociative disorders -- Treatment; Post-traumatic stress disorder -- Complications; Psychic trauma -- Complications; Post-traumatic stress disorder -- Complications -- Treatment; Psychic trauma -- Complications -- Treatment